The effect of sowing times and pre-sowing seed treatment on field germination and yield of soybean varieties with different vegetation periods (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The article presents the results of three years of research on the complex effect of sowing dates and pre-sowing seed treatment on the formation of crop density, field germination, and yield of soybean varieties with different growing seasons.
Keywords: soybean; variety; sowing date; field germination; yield